Identifikasi Kinerja IPAL Komunal Domestik Terbangun Sebelum Tahun 2012 di Kota Besar Indonesia (Studi Kasus IPAL RW 17 Melong Kota Cimahi) - Fahry Rachmayadi; Moh. Rangga Sururi (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Waste water treatment installation (WWTP) in RW 17 Melong Cimahi City according to UPTD Cimahi City Wastewater was built before 2016, so it was designed with reference to the old standard of wastewater quality, namely the Environment Ministry Regulation No. 5 of 2014. The aim of this study is to evaluate the performance of the municipal WWTP built before the latest regulation namely PermenLHK No. 68 Year 2016 came into force. In this study, the identification of the pipe network path and the measurement of wastewater discharge is done directly to compare with the theoretical calculation of discharges. Then the WWTP performance analysis is performed by comparing the treatment results with the quality standards. The results of the study showed that the parameters TSS, Ammonia, COD, BOD, Total Coliform did not meet the standard quality standards and only pH and Fatty Oils matched the quality standards. The study also identified the operational patterns that caused the condition to occur.